The Role of Financial Literacy in Enhancing the Impact of Financial Inclusion on Economic Growth Among Sub-Saharan Africa Countries - Akrofi, Kwaku Sarbeng-Adjebeng; Ocansey, Evans O. N. D; Asamoah, Felix Oppong (Archives of Business Research, 2025)
This study investigates the role of financial literacy in shaping the relationship between financial inclusion and economic growth across 49 Sub-Saharan African (SSA) countries over the period 2003 to 2023. The primary objective is to evaluate whether financial literacy enhances the impact of financial inclusion on economic performance. Specifically, the study examines three dimensions: the direct effect of financial inclusion on growth, the moderating influence of financial literacy, and the direct contribution of financial literacy to economic expansion. Employing a quantitative research design, the study uses Generalized Method of Moments (GMM) dynamic panel estimations to address issues of endogeneity and reverse causality. Secondary data were sourced from global databases including the World Bank, IMF, and Klapper and Lusardi’s (2020) financial literacy indicators. Variables such as inflation, unemployment, trade openness, and institutional quality were controlled for, ensuring robust empirical estimation. The findings reveal that financial inclusion alone does not significantly enhance economic growth in the absence of adequate financial literacy. However, when financial literacy is introduced as a moderator, the interaction term exhibits a significant and positive relationship with growth. Additionally, financial literacy by itself is also found to positively influence growth outcomes. These results have profound implications for financial sector policy, indicating that financial capability must be built alongside access. Thus, policymakers are encouraged to integrate financial literacy into national financial inclusion strategies, ensuring that economic empowerment efforts are both inclusive and transformative.